Cyber Community Towards Society 5.0 And The Future Of Social Reality - Burhan Bungin; Monika Teguh; Muhammad Dafa (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract—In cyber community towards the Society 5.0 era, the use of industrial technology 4.0, especially communication media technology plays an important role. The information era causes digital communication media technology to develop very rapidly and encourage the birth of digital media that have real time capabilities and create new media. Currently mass media institutions that are not innovative are experiencing a fall. Then the existence of the construction of reality is also increasingly obscured by the mixing of life in the real world with the virtual world. Therefore, the study wants to criticize the existence of reality in the midst of the development of communication technology that is so fast. This study uses the interview method in collecting data and analyzing it using the narrative method. The results of this study are that in society 5.0 and industrial technology 4.0, a pseudo social reality constructed by communication technology media causes mass media to die, social harmony is confused and even lost, and hoaxes are attacks on harmony.technological advances in industry 5.0 increase above 70%.